APLIKASI WAKAF MU’AQQAT DI MALAYSIA: ANALISIS KRITIKAL DARI PERSPEKTIF PEMBANGUNAN EKONOMI ISLAM : The Application of Temporary Waqf in Malaysia: Critical Analysis from the Perspective of Islamic Economics Development - Alin @ Nordin, Noor Ain; Ab Rahman, Asmak; Sukmana, Raditya (Jurnal Syariah, 2025)
The overall potential of wakaf mu’aqqat (temporary waqf) as an instrument to enhance and grow the Islamic economy has shown significant impact. It can be carried out through multiple methods based on the suitability of the situation in order to achieve the desired results that would impact the general public. Although, this has yet to be practice widely in Malaysia due to different mazhab understanding and holdings, it could play a crucial role in enhancing the current wakaf structure which will be in line with maqasid syariah reflective of permanent wakaf. Nevertheless, this instrument has yet to be tabled and explore thoroughly. Thus, this research was carried out meticulously to observe as well as record the impact in line with maqasid syariah from the perspective of the Islamic economies growth through the application of wakaf mu’aqqat. This study employed a data collection methodology combining library research and interviews, which analysed using thematic content analysis. The research is completed in hopes that it will be a future guide and reference in tandem to the efforts of increasing the participation of wakaf. This will directly or indirectly contribute to the growth of the Islamic economy in Malaysia that would benefit the Islamic society.